The complete chloroplast genome of a commercially exploited ornamental plant, Bougainvillea glabra (Caryophyllales: Nyctaginaceae). Issue 2 (3rd July 2019) - Ni, Jianzhong; Lee, Shiou Yih; Hu, Xing; Wang, Wei; Zhang, Jifang; Ruan, Lin; Dai, Seping; Liu, Guofeng
Abstract: Bougainvillea glabra is an ornamental plant that is domesticated in many tropical and sub-tropical countries. The focus on its breeding programmes has overshadowed genetic studies of this important species. In this study, we reported on the complete chloroplast (cp) genome of B. glabra . The cp genome is 154, 763 bp in size, comprised of a large single copy (LSC) region of 85, 921 bp, a small single copy (SSC) region of 18, 018 bp, and a pair of inverted repeat (IR) regions of 25, 412 bp each. A total of 131 genes were predicted, including 37 tRNA, 8 rRNA, and 86 protein-coding genes. Phylogenetic analysis revealed that B. glabra is placed under Nyctaginaceae and sister to B. spectabilis under a strong bootstrap support.